ENVIRONMENTAL DETERMINANTS IN DESIGNING FACILITIES OF THE HOSPITALITY INDUSTRY - Піддубний, Володимир; Тарасюк, Галина; Чагайда, Андрій; Радченко, Юрій (SWorldJournal, 2024)
The establishments of the hospitality industry and consumers of their services are increasingly aware of the growing environmental problems every year, which prompts hotel complexes to look for ways to reduce the impact on the environment. By the term "e